Draft genome sequence data of Bacillus subtilis strain 9407, isolated from healthy apples in China - Zeng, Qingchao; Xie, Jianbo; Li, Yan; Gu, Xiaofei; Wang, Qi (Data in brief, 2020)
Bacillus subtilis strain 9407 is an endophyte which was isolated from healthy apples from an infested orchard that exhibits strong inhibitory activity against Botryosphaeria dothidea. Whole-genome sequencing of B. subtilis 9407 was performed using the Illumina Hiseq platforms. Here, we report the draft genome sequence of B. subtilis strain 9407 containing 16 scaffolds (4,062,615 bp), 4033 coding sequences, and an average 43.66% G + C content. The genome contains genes responsible for the production of several bioactive secondary metabolites, including the lipopeptides fengycin and surfactin. The genome information will provide fundamental knowledge of the organism. This whole-genome shotgun data has been deposited at DDBJ/EMBL/GenBank under the accession numbers PISO00000000.